Pegaruh Model Pembelajaran Picture And Picture Terhadap Kemampuan Menulis Teks Narasi Di Sekolah Dasar - Desta Tiara Rahmawan; Indah Nurmahanani; Acep Ruswan (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
It is still low in narrative text, because writing the text of the student narrative is still difficult to select raw words when writing an idea, there are still words repeated, and intersentences are less continuous. The study aims to find out, (1) the ability to write a narrative text on elementary school students before applying a picture and picture learning model. (2) the ability to write a narrative text for elementary school students after applying the debriefing model of picture and picture. (3) the influence of the picture and picture learning model on the ability to write narrative text in elementary school students. This kind of research is an experiment with preexperiment type one group predisposed posttest type. The population in this study represents the entire v class as many as 14 students in one of the primary schools in purwakarta. Sampling retrieval uses an impressive sampling technique which is that all v-grade students number 14. The data gathered in the study is from pretest and student posttes. The data obtained has been analyzed using a few tests that are, product moment prerequisite test, product moment coordinated, simple linear regression, hypothesis and n-gain. Studies have shown that the ability to write narration texts before and after treatment by applying a picture and picture model has improved. Based on the results of studies, it could be said that the ability to write the text of the student narrative increases after treatment. Thus, in this study it is conclusive, (1) the students' ability to write a narrative text before applying the picture and picture learning model at an average of 66 falls under considerable skill. (2) students' ability to write a narrative text after applying the picture and picture learning model with an average value of 78 falls into the skilled category. (3) there is the influence of the learning model picture and picture on the ability to write the text of the student narrative. Keyword: Picture and Picture Learning Model, Narrative Text Writing Skill